Disputes within the agrarian issue in Brazil: subsidies to discuss the Education in/of the Country (Terr@ Plural, 2020)
The understanding of the countryside as a place of conflict and territorial disputes is an issue that has been constantly deconstructed by the popular media, which ends up being commonly proclaimed as the domain of the extensive production of agribusiness. However, in this study another perspective of the countryside is placed, a territory of life, of culture, of people, in addition to the coldness in the so-called ‘green deserts’, where public policies, although quite small, may also be sought and conducted to enable the peasant way of life. This research presents a brief diagnosis of the Brazilian countryside a reflection that is displaced from the dichotomous sense of the countryside since it is known that Brazil, a country with continental extensions, has full capacity to support capitalists, and peasant agriculture. Thus, a debate enshrined in the dialectical bias of these territories. Finally, the issue of peasant education is taken as a specificity, stressing the importance of this public policy to strengthen the resistance strategies of the peasant movements, since the structured peasant education is a tool to crystallize the identity of social mobilization and future generations formation.
Keywords: Peasantry; Peasant education; Territory; Autonomy